Effect of additive cashew grain size on brake performance of non-asbestos linings - Karaca, Faruk; Can, Ilhan (Korean Soc Mechanical Engineers, 2021)
The most important parameter in lining production is determining and combining the material composition. The amount of these materials in the composition affect the physical properties of the materials such as the wear resistance, the friction coefficient, and the observing of the optimum temperature distribution. The purpose of this study was to investigate the effect of grain size on the wear characteristics of the lining and to examine the usability of cashew as an organic material, in automobile brake linings. The cashew grain sizes of 50 mu m, 75 mu m, and 125 mu m are adjusted. The wear rate has increased with increasing grain size. The friction coefficient has changed considerably with the grain size of cashew. Besides, the brake temperature presented valuable variation like friction coefficient. As a conclusion, the cashew grain size affected the braking performance significantly, as expected.
Keywords: Brake lining; Cashew; Friction coefficient; Grain size; Wear